대장내시경 검사를 위한 적절한 장정결제 선택 (The Ewha Medical Journal)
Colonoscopy is commonly used to screen for and diagnose colorectal disease, and adequate bowel preparation is crucial to its quality. As bowel preparation regimens vary, it is important that clinicians understand each and select the proper one for each patient. Accordingly, here we investigated recent studies and describe how to choose the optimal bowel preparation regimen. We detail composition, dosages, efficacy, contraindications, and precautions of commonly used regimens including 4 L polyethylene glycol (PEG), 2 L PEG+ascorbic acid, 1 L PEG+ascorbic acid, trisulfate (oral sulfate solution/tablets), and sodium picosulfate/magnesium citrate. Here we describe that the most recently introduced 1 L PEG and oral sulfate tablets, which were developed to improve convenience and compliance, differ in composition and efficacy between South Korea and foreign countries. This review presents new evidence of and differences among products to increase clinician understanding.